Edukasi Vaksinasi Human Papilloma Virus sebagai Upaya Pencegahan Kanker Serviks pada Ibu Pemberdayaan dan Kesejahteraan Keluarga - Khoerudin, Ahmad; Cahyaningrum, Etika Dewi; Marifah, Atun Raudotul (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Cervical cancer is a serious reproductive health issue in Indonesia, with Human Papillomavirus (HPV) infection being the leading cause. Suspected cervical cancer cases in Banyumas Regency remain high, including 13 cases in Sudimara Village in 2023-2024. The lack of knowledge of PKK mothers in the village regarding cervical cancer prevention and the HPV vaccine underscores the urgency of education to increase their understanding. Objective: This Community Service (PkM) activity aims to increase the knowledge of PKK mothers in Sudimara Village about HPV vaccination as an effort to prevent cervical cancer. Method: The PkM program involved 24 participants, and the education began with a pre-test. The educational method used lectures, discussions, and questions and answers, supported by visual media such as PowerPoint presentations, leaflets, and videos, followed by monitoring and evaluation. Result: The pre-test results showed an average knowledge score of 49.71, with the majority (76.67%) of participants having poor knowledge. After the education, the average post-test score increased significantly to 78.35, with the majority (79.17%) of participants having high knowledge. Conclusion: Based on the pre-test and post-test results, there was an increase in knowledge levels from before to after the education, with the average pre-test to post-test score increasing by 28.64. The implementation of cervical cancer prevention education through the HPV vaccine among PKK mothers showed positive results in increasing knowledge.